2017
DOI: 10.1177/2050312117699146
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effect profile comparison of pain regimens with and without intravenous acetaminophen in total hip and knee arthroplasty patients

Abstract: Background:The use of adjunct, non-opioid agents is integral for pain control following total hip and knee arthroplasty. Literature comparing safety profiles of intravenous acetaminophen versus opioids is lacking.Objective:To determine whether there is a difference in frequency and type of adverse effects between intravenous acetaminophen–treated and non-intravenous acetaminophen–treated patients. Primary safety endpoints included any adverse effect noted in the electronic medical record post-surgically. Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In the primary search, 228 articles were reviewed. Finally, 3 RCTs [ 12 – 14 ] and 1 non-RCTs [ 15 ] met eligibility criteria of the present meta-analysis. Overall, the 4 studies included 534 patients in the acetaminophen groups and 331 patients in the control groups.…”
Section: Resultsmentioning
confidence: 99%
“…In the primary search, 228 articles were reviewed. Finally, 3 RCTs [ 12 – 14 ] and 1 non-RCTs [ 15 ] met eligibility criteria of the present meta-analysis. Overall, the 4 studies included 534 patients in the acetaminophen groups and 331 patients in the control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on outcomes following TKA using traditional approaches to postoperative analgesia have reported extended opioid use and delayed functional recovery. In recent studies of patients receiving various postoperative treatments (e.g., oral medications, local anesthetic-based nerve blocks, transcutaneous electrical nerve stimulation, intravenous acetaminophen), average opioid consumption is often greatest during the immediate postoperative period (e.g., average daily morphine equivalent dosage [MED] of approximately 30-170 mg during postoperative days 0-3) (7,(39)(40)(41)(42)(43); fewer than 30% of patients had ceased opioid use by four weeks following TKA, and the median time to opioid cessation was approximately 45-60 days (4,6,7). In the present study, average daily MED during postoperative days 0-3 was approximately 22 mg, a majority (4 of 7; 57%) of subjects reported opioid cessation within the first week following surgery, and the median time to opioid cessation was six days.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular benefit, Singla et al [12] demonstrated that patients receiving IV acetaminophen consumed less than half the rescue opioids than those receiving placebo following total hip arthroplasty. However, in a retrospective chart review, Gallipani et al [24] did not appreciate a decrease in narcotic use in patients given IV acetaminophen following total joint arthroplasty. Other studies by Kelly et al [25] and Nwagbologu et al [26] did not find a decrease in opioid consumption in patients who received IV acetaminophen following TKA.…”
Section: Discussionmentioning
confidence: 98%
“…Despite these conflicting studies, a prospective, randomized trial [21] and retrospective database study [9] have demonstrated that patients receiving IV acetaminophen had fewer adverse events after total joint arthroplasty. However, Gallipani et al [24] in a retrospective chart review demonstrated an increase in adverse events in patients given IV acetaminophen following total joint arthroplasty. These studies vary in their conclusions, and it is incumbent upon the treating surgeon to be aware of these conflicting reports on the utility of IV acetaminophen in the literature.…”
Section: Discussionmentioning
confidence: 99%